Pengaruh Dimensi Kualitas Pelayanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Pada Yayasan Agaphe Banjarmasin - Albert Risdyanto; Asmu'i Asmu'i (JURNAL BISNIS DAN PEMBANGUNAN, 2023)
Organizations must continue to develop in order to provide customers with the highest possible standard of service given the competition among training institutions in Banjarmasin and the variety of training topics that will be covered at Yayasan Pusat Pelatihan Motivasi & Pengembangan Sumber Daya Manusia AGAPHE Banjarmasin in the months and years to come. In this study, the Foundation Training Center for Motivation & Human Resource Development Agaphe Banjarmasin's training program is being examined to see what impact student satisfaction has on students' commitment to it. 194 people in all completed the survey for this study. SmartPLS software was used for the data analysis. The findings demonstrated that assurance and empathy dimensions have a favorable and significant direct impact on trainees' levels of satisfaction, while assurance and empathy dimensions have a favorable and major direct impact.  Keywords: assurance, emphathy, responsiveness, satisfaction, and loyalty